Trees, Shrubs and Grasses on Saline Soils of Indo-Gangetic Plains - Singh, Kalyan; Jha, M. N. (Indian Forester, 1993)
Studies on site suitability and tolerance limits to soil salinity of trees, shrubs and grasses were conducted under field conditions in Social Forestry Divisions of Mathura and Manipur(U.P.). Prosopis juliflora in association with bushes (Tamarix sp., Salvadora oleoides, Capparis decidua and Acacia leucophloea) was able to grow on fine mixed hyperthermic strongly saline Natric Camborthids which had Ece < 40 dS m − 1 and CaCO3 < 12% in the rooting zone of 10-130cm soil depth; moderately deep ground water table 2-3m) and Kankar/clay pan beyond 80 cm soil depth. The sites under fine-loamy mixed hyperthermic Typic Salorthids had higher levels of Ece, pH, CaCO3, compact and impervious Kankar pan within 60 cm soil depth, poor drainage, shallow ground water table(< 2m), thick salt encrustation and were devoid of vegetation. Comparatively,Acacia nilotica and natural Crateva adansonii, Anthocephalus indicus, Diplachne fusca, Cynodon dactylon and Sporabolus marginatus could tolerate Ece < 27 dS m−1, pH < 7.9, CaCO3 < 5% with absence of Kanka/clay pan in the rooting zone of 28 170cm of coarse-loamy mixed hyperthemic highly saline Natric Camborthids. Mixed species like Dalbergia sissoo, Pongamia pinnata, Holoptelea integrifolia, Eucalyptus hybrid, Cassia siamea and natural Cryptostegia grandiflora, Prosopis cineraria, Capparis zeylanica, Saccharum spontaneum grew on fine-loamy mixed hyperthermic highly saline Typic Camborthids and Coarse-loamy mixed hyperthermic moderately saline Aeric Halaquepts which had ECe < 18.5 ds m−1, pH around 8.5 and CaCO3 < 5% in the rooting zone 12-180 cm of soil depth without Kankar/ clay pan. High salt concentration in top 10 or 28 cm soil did not adversely affect the plant growth. This study will help in identification of most suitable plant species for a given site in saline areas in order to have best land use.